(untitled) (Canadian Hematology Today, 2024)
Initial adult acute myeloid leukemia (AML) treatment is generally divided into two intensity-based approaches based on patient (age, comorbidities, patient preference, among others) and disease (genetic risk, natural history [de novo vs. secondary AML (sAML) vs. therapy-related AML (tAML)], among others) factors. For those patients deemed appropriate for intensive treatment, current approaches result in the achievement of a complete remission (CR) in a majority of cases. In such patients, remissions are generally consolidated by further cycles of chemotherapy, or by additional chemotherapy followed by an allogenic hematopoietic stem cell transplant (alloHSCT), as appropriate, depending on patient and disease factors as above.